Focal cryotherapy of localized prostate cancer: a systematic review of the literature. Issue 11 (November 2014) - Shah, Taimur Tariq; Ahmed, Hashim; Kanthabalan, Abi; Lau, Benjamin; Ghei, Maneesh; Maraj, Barry; Arya, Manit
<x xml:space="preserve">Abstract</x> Radical/whole gland treatment for prostate cancer has significant side-effects. Therefore focal treatments such as cryotherapy have been used to treat localized lesions whilst aiming to provide adequate cancer control with minimal side-effects. We performed a systematic review of Pubmed/Medline and Cochrane databases' to yield 9 papers for primary focal prostate cryotherapy and 2 papers for focal salvage treatment (radio-recurrent). The results of 1582 primary patients showed biochemical disease-free survival between 71–93% at 9–70 months follow-up. Incontinence rates were 0–3.6% and ED 0–42%. Recto-urethral fistula occurred in only 2 patients. Salvage focal cryotherapy had biochemical disease-free survival of 50–68% at 3 years. ED occurred in 60–71%. Focal cryotherapy appears to be an effective treatment for primary localized prostate cancer and compares favorably to radical/whole gland treatments in medium-term oncological outcomes and side-effects. Although more studies are needed it is also effective for radio-recurrent cancer with a low complications rates.